The effects of marketing and market orientation on economical and financial performance in portuguese SME - Correia, Ricardo Jorge (2013)
The market orientation (MO) degree has been studied for scientific and academic community, occupying actually a prominent place at the marketing research field. In a stakeholder’s value creation perspective and in highly competitive environments, the development of a customer and market-oriented culture may represent the frontier to the companies’ survival, specially micro and medium enterprises (SMEs). This paper includes the results of an empirical research about marketing, market orientation degree and environmental variables such as competitive intensity and market turbulence as factors that can influence the economic and financial performance of Portuguese micro and small companies located in a rural area. The results indicate that: (a) marketing is seen by these companies as an accessory, not deserving an attention materialized in practical actions that can be considered like strategic, (b) at market orientation level, the market information affects positively some performance indicators, (c) and economical and financial performance is superior in conditions of highly market turbulence and there is a negative relationship between competitive intensity and the companies ratio turnover/total assets.